Role of Price and Quality in Shaping Consumer Perception of Shoes Brands: A Case of Kathmandu Valley - Thapa, Prerak; Rawat, Ramesh (Nepalese Journal of Economics, 2025)
This study examines the role of price and quality in shaping consumer perception in shoes brands in Kathmandu valley. Customer perception of quality is the dependent variable. The selected independent variables are price range, brand reputation, product design and innovation, marketing and advertising strategies, and socio economic status for consumer. The primary source of data is used to assess the opinions of respondents regarding price range, brand reputation, product design and innovation, marketing and advertising strategies, and socio economic status for consumer and customer perception of quality. The study is based on primary data of 119 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of role of price and quality in shaping consumer perception if shoes brands in Kathmandu valley. The study showed a positive impact of price range on customer perception of quality. It indicates that repair and maintenance service leads to increase in customer perception of quality. Similarly, the study showed a positive impact of spare part supply on customer perception of quality. It indicates that easily available of spare part supply leads to an increase in customer perception of quality. Likewise, the study also revealed a positive impact of services camp on customer perception of quality. It indicates that provision of services camp leads to an increase in customer perception of quality. Further, the study observed a positive impact of mileage on customer perception of quality. It indicates that higher the mileage, higher would be the customer perception of quality. In addition, the study observed a positive impact of price on customer perception of quality. It indicates that affordable price leads to an increase in customer perception of quality.